On the Environmental Factors Affecting the Structural and Cytotoxic Properties of IAPP Peptides - Marianna Flora Tomasello; Alessandro Sinopoli; Giuseppe Pappalardo (Journal of Diabetes Research)
Pancreatic islets in type 2 diabetes mellitus (T2DM) patients are characterized by reduced β-cells mass and diffuse extracellular amyloidosis. Amyloid deposition involves the islet amyloid polypeptide (IAPP), a neuropancreatic hormone cosecreted with insulin by β-cells. IAPP is physiologically involved in glucose homeostasis, but it may turn toxic to β-cells owing to its tendency to misfold giving rise to oligomers and fibrils. The process by which the unfolded IAPP starts to self-assemble and the overall factors promoting this conversion are poorly understood. Other open questions are related to the nature of the IAPP toxic species and how exactly β-cells die. Over the last decades, there has been growing consensus about the notion that early molecular assemblies, notably small hIAPP oligomers, are the culprit of β-cells decline. Numerous environmental factors might affect the conformational, aggregation, and cytotoxic properties of IAPP. Herein we review recent progress in the field, focusing on the influences that membranes, pH, and metal ions may have on the conformational conversion and cytotoxicity of full-length IAPP as well as peptide fragments thereof. Current theories proposed for the mechanisms of toxicity will be also summarized together with an outline of the underlying molecular links between IAPP and amyloid beta (Aβ) misfolding.